2018
DOI: 10.1111/omi.12225
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NLRP3 inflammasome in macrophages by mycoplasmal lipoproteins and lipopeptides

Abstract: The NLRP3 inflammasome, an intracellular sensor consisting of the nucleotide-binding oligomerization domain-like receptor family, pyrin domain containing 3 (NLRP3), the adaptor protein apoptosis-associated speck-like protein containing a caspase-recruitment domain (ASC), and procaspase-1, plays critical roles in host defense against microbial pathogens by inducing production of interleukin-1β (IL-1β) and IL-18. Mycoplasma salivarium and Mycoplasma pneumoniae cells activated murine bone marrow-derived macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 65 publications
(194 reference statements)
2
10
0
Order By: Relevance
“…We previously showed that MsLP, MpLP and FSL-1 activate the NLRP3 inflammasome to produce IL-1b in BMMs. 35 Inflammasome-dependent cell death, i.e. pyroptosis, is a mechanism that involves IL-1b release into the extracellular space.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously showed that MsLP, MpLP and FSL-1 activate the NLRP3 inflammasome to produce IL-1b in BMMs. 35 Inflammasome-dependent cell death, i.e. pyroptosis, is a mechanism that involves IL-1b release into the extracellular space.…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that the artificial delivery of FSL-1 into the cytosol of BMMs using the PULSin protein transfection reagent enhances the IL-1b-inducing activity. 35 Accordingly, under this assay condition, both active Figure 4. Mycoplasmal lipopeptide-induced interleukin-1b (IL-1b) release is dependent on plasma membrane permeabilization.…”
Section: Fsl-1 Transfection By Pulsin Cleaves Gsdmdmentioning
confidence: 99%
See 3 more Smart Citations